‘Feels (Not) Like At Home’: Perlakuan di Lapas, Interaksi Sosial dan Harapan Pengguna Narkoba Mantan Narapidana - Riskiyani, Shanti (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
Abstract The estimation of HIV prevalence among prisoners is 24 times higher than that of the general population in Indonesia. This high HIV prevalence in a number of prison in Indonesia is caused by the many drug users who become prisoners (Kemenhukham2010). The existence of Harm Reductionprogram in Indonesia plays a significant role in the success of the reduction in the risk of HIV transmission through injecting among drug users. This article is focused on thesocial interaction experienced by drug users when they are sentenced and after serving a sentence. Despite the fact that Ditjenpas declares that prisoners are entitled to obtain appropriate treatment, most drug users, particularly injecting drug users, feel that they are treated differently from other prisoners as well as warden due to their drug users status, especially when they access health services. Thus, they end up learning helplessly because of their prisoner status. Drug users prefer to be isolated from other non-drug user prisoners since the interaction with the latter has given them a chance ‘to learn’ about other kinds of criminals. Interaction among drug users themselves is relatively fine, and they share ‘sense of togetherness’ and ‘sense of belongingness’ led to their security in the prison. But this is not the case between drug users and non-drug use prisoners. The latter tends to stigmatize. Family support when they are sentenced and after serving a sentence is highly expected because family plays a significant role to help them dealing with their addiction andthe effort to get out from drug use vicious circle, particularly for their healthcare. Many support by their family, others are neglected. But, family can also be the one who supports their drug using habit in the secure atmosphere (named home) to secure family shame. When they release from prison, many expect to be accepted as other members of the society and are included in surrounding social activities. Others prefer to be socially neglected because they perceive that others concern potentially lead to social stigma Keywords: drugs, ex-convict, social interaction, HIV, prisoners.